Use of intravenous etomidate to control acute psychosis induced by the hypercortisolaemia in severe paediatric Cushing's disease - Chan, L; Vaidya, M; Westphal, B; Allgrove, J; Martin, L; Afshar, F; Hindmarsh, P; Savage, M; Grossman, AB; Storr, H (2011)
Background: Psychosis secondary to paediatric Cushing's disease (CD) is extremely rare and presents a significant management challenge. Method: We report a 14.7-year-old CD patient with acute psychosis and self-inflicted injuries following failed transsphenoidal pituitary surgery. Her mental state rapidly deteriorated precluding medical therapy. Results: Emergency intravenous low-dose etomidate infusion (3-3.5 mg/h) with dose titration according to the serum cortisol combined with a hydrocortisone infusion, in an intensive care setting, was effective in controlling the hypercortisolaemia. Her mental state improved with normalisation of her cortisol levels enabling oral administration of ketoconazole and bilateral adrenalectomy to be performed. Conclusion: This case illustrates the safe and effective use of a low-dose etomidate infusion in an unusual case of paediatric CD. Copyright © 2011 S. Karger AG, Basel.